2014
DOI: 10.1177/0047287514546224
|View full text |Cite
|
Sign up to set email alerts
|

Online Marketing Strategy and Market Segmentation in the Spanish Rural Accommodation Sector

Abstract: The present work tests the effect of the online differentiation strategies employed by rural accommodation enterprises (RAEs) among different segments of the tourist population. More specifically, the following aspects are identified: (1) the different tourist segments that undertake rural tourism; (2) the various online differentiation strategies adopted by RAEs; and (3) the effect of these online differentiation strategies on tourist behavior, by segment (in terms of perceived value). The results reveal that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 109 publications
1
16
0
1
Order By: Relevance
“…The local authorities managing rural tourism must therefore implement policies to promote its development. For Polo (2010), the development of the rural tourist activity is very suitable for improving the development of the rural areas, likewise Marzo-Navarro (2017) stated that rural tourism promotes the development and economic growth of the destination areas, for which it is a priority to achieve the objectives of economic, sociocultural, and environmental sustainability. The World Tourism Organization (UNWTO) (2021) has recognized that "tourism is one of the driving forces of global economic growth and is currently responsible for the creation of 1 in 11 jobs.…”
Section: Introductionmentioning
confidence: 99%
“…The local authorities managing rural tourism must therefore implement policies to promote its development. For Polo (2010), the development of the rural tourist activity is very suitable for improving the development of the rural areas, likewise Marzo-Navarro (2017) stated that rural tourism promotes the development and economic growth of the destination areas, for which it is a priority to achieve the objectives of economic, sociocultural, and environmental sustainability. The World Tourism Organization (UNWTO) (2021) has recognized that "tourism is one of the driving forces of global economic growth and is currently responsible for the creation of 1 in 11 jobs.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some of the visitors have already complained that the photographs used for the promotion of the area in the social media were different from what they saw. POLO PEÑA et al (2016) suggested that rural tourism providers must pay particular attention to the information they need to transfer to potential visitors regarding the product (image) they want to promote through their web-sites. By providing proper information and images, they will not only avoid underestimation or overestimation but also use their resources more efficiently (POLO PEÑA et al, 2016) and for branding.…”
Section: Resultsmentioning
confidence: 99%
“…POLO PEÑA et al (2016) suggested that rural tourism providers must pay particular attention to the information they need to transfer to potential visitors regarding the product (image) they want to promote through their web-sites. By providing proper information and images, they will not only avoid underestimation or overestimation but also use their resources more efficiently (POLO PEÑA et al, 2016) and for branding. This is why it is necessary to pay attention the images presented by the popular mass media and consider how they relate to rural tourism (AITHAL & ANIL, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…the rural development of Lithuania is determined using economic factors and calculations. (Snieška et al, 2014)) or they can describe a marketing strategy for the industry of a country (Chen et al, 2013). In 22.47% of cases, the studied area comprises one single destination or the comparison of two adjacent destinations.…”
Section: Resultsmentioning
confidence: 99%
“…Th e interest in tourists, their characterization and segmentation have remained constant throughout the examined 15 years (8.82%). Some of the studies concentrated on tourists have as their primary purpose segmentation and profi ling of motivation of rural tourists in South Korea (Park & Yoon, 2009), Finland (Pesonen & Komppula, 2010), Cyprus (Farmaki, 2012), Taiwan (Chen et al, 2013), andGambia (Rid et al, 2014). François Bel and co-authors (2015) carried out the activity-based segmentation of visitors' stays in three rural regions of France, while Lourdes Molera et al (2007) provide a better understanding of the demand for rural tourism through market segmentation analysis.…”
Section: Resultsmentioning
confidence: 99%